A comprehensive review on diabetic foot ulcer addressing vascular insufficiency, impaired immune response, and delayed wound healing mechanisms - Aditya, Chavan; Bukke, Sarad Pawar Naik; Anitha, Kuttiappan; Meeraraje, Pandhare; Goruntla, Narayana; Yadesa, Tadele Mekuriya; Onohuean, Hope (Frontiers in Pharmacology, 2025)
Diabetic foot ulcers (DFUs) continue to represent one of the most significant and costly complications related to diabetes mellitus, posing serious challenges to healthcare systems and resulting in considerable morbidity rates. This narrative review explores the complex pathophysiology of DFUs, focusing on the interplay between peripheral neuropathy, vascular insufficiency, and a weakened immune response, all of which contribute to delayed wound healing. Neuropathy leads to a loss of protective sensation, causing unnoticed repetitive injuries, while both microvascular and macrovascular complications reduce tissue perfusion and hinder angiogenesis. Additionally, immune dysfunction and exaggerated inflammatory responses raise the occurrence of infection and negatively affect the healing process. The clinical manifestation, progression, and key risk factors of DFUs were discussed in this review, emphasizing the importance of early detection, careful foot care, and routine screening in individuals who are at risk. Numerous therapeutic approaches are reviewed, including wound debridement, sophisticated wound dressings, offloading techniques, glycemic control, and adjuvant therapies such as growth factor administration, hyperbaric oxygen therapy, and negative pressure wound therapy. For optimal results, a multidisciplinary team combining of vascular surgeons, podiatrists, endocrinologists, and wound care specialists was included. The analysis also points out that promising advancements in bioengineered skin substitutes, intelligent dressings, and regenerative medicine hold promise for the treatment of DFU in the future. Self-monitoring, appropriate footwear, and patient education are all important components of prevention, which remains a fundamental strategy. In the clinical management of DFUs, this narrative review incorporates the most recent research and highlights the value of proactive, customized, and multidisciplinary approaches.